Phototropin Interactions with SUMO Proteins. (17th February 2021) - Łabuz, Justyna; Sztatelman, Olga; Jagiełło-Flasińska, Dominika; Hermanowicz, Paweł; Bażant, Aneta; Banaś, Agnieszka Katarzyna; Bartnicki, Filip; Giza, Aleksandra; Kozłowska, Anna; Lasok, Hanna; Sitkiewicz, Ewa; Krzeszowiec, Weronika; et al.
Abstract: The disruption of the sumoylation pathway affects processes controlled by the two phototropins (phots) of Arabidopsis thaliana, phot1 and phot2. Phots, plant UVA/blue light photoreceptors, regulate growth responses and fast movements aimed at optimizing photosynthesis, such as phototropism, chloroplast relocations and stomatal opening. Sumoylation is a posttranslational modification, consisting of the addition of a SUMO (SMALL UBIQUITIN-RELATED MODIFIER) protein to a lysine residue in the target protein. In addition to affecting the stability of proteins, it regulates their activity, interactions and subcellular localization. We examined physiological responses controlled by phots, phototropism and chloroplast movements, in sumoylation pathway mutants. Chloroplast accumulation in response to both continuous and pulse light was enhanced in the E3 ligase siz1 mutant, in a manner dependent on phot2. A significant decrease in phot2 protein abundance was observed in this mutant after blue light treatment both in seedlings and mature leaves. Using plant transient expression and yeast two-hybrid assays, we found that phots interacted with SUMO proteins mainly through their N-terminal parts, which contain the photosensory LOV domains. The covalent modification in phots by SUMO was verified using an Arabidopsis sumoylation system reconstituted in bacteria followed by the mass spectrometry analysis. Lys 297 was identified as the main target of SUMO3 in the phot2 molecule. Finally, sumoylation of phot2 was detected in Arabidopsis mature leaves upon light or heat stress treatment.